Evaluation and Demonstration of Potchefstroom Koekoek Chicken in and around Mehoni Areas of Southern Tigray zone, Ethiopia (Global Journal of Science Frontier Research, 2018)
The evaluation and demonstration of Potchefstroom Koekoek Chicken were conducted in and around Mehoni Areas of Southern Tigray Zone, Ethiopia. Participant farmers were selected purposively based on their interest to construct poultry house; to cover other relevant poultry package costs, record the required data and to the most was identified by Mehoni Agricultural Research Center in Collaboration with the Raya Azebo Woreda Bureau of Agriculture and Rural Development Poultry experts based on the information given by national poultry research coordinating team (DZARC Poultry Team). The Survival of chicks during the first eight weeks of brooding using 40-watt bulb and traditional pot heater at farmers management condition were 82.86% (319 were survived out 385). On average about 94.56% of the chicken were survived to up to 2nd eight weeks of age while the overall survivability has attained to be 78.18% in the study areas. The average age at first egg laying was found to be 6.48 months and average weight of eggs at first laying and 5% production stage was 39.01g and 40.30g. Similarly, the average weight of egg of each participant farmers at 50% and Peak egg production stage was approved to be 43.93g and 48.77g, respectively. The average weight of male and female Koekoek chicken at 20 and 72 weeks of age was 1.40kg, 1.01kg, 2.70kg and 1.46kg respectively. The egg production per chicken has ranged from 124 to 186 with an average of 156.29 under scavenging farm condition. The average feed supplementation per chicken per day was 54.21g up to the intended production stage (72 weeks of age). The average profit of each participating farmers in the entire study period was 8927.34 Birr. Based on the result of the study, the major challenges were Transport stress and mechanical damage, Predator attack and flood, Shortage and cost of local and formulated feeds (drought existed), insufficient management(more emphasis to irrigation) and Diseases. On the other hand, the main oppor
Keywords: koekoek breed; survivability; egg production; scavenging; challenge; opportunity; perception and farmer’s management